Odpowiedzi

Najlepsza Odpowiedź!
2009-11-15T21:28:49+01:00
X³-2x²-3x+6=x(x²-3)-2(x²-3)=(x²-3)*(x-2)=(x+√3)*(x-√3)*(x-2)
miejsca zerowe:√3;-√3;2
2009-11-15T21:31:51+01:00
X³-2x²-3x+6 =0
x³ - 3x - 2x² +6 =0
x (x² - 3) - 2(x² - 3) =0
(x² - 3)(x - 2) = 0
(x² - 3) = o (x - 2) = 0
(x - pierwiastek z 3)(x + pierwiastek z 3) =o (x - 2) = 0
x=pierwiastek z 3 x= - pierwiastek z 3 x= 2
2009-11-15T21:33:11+01:00
F(x)=x³-2x²-3x+6=x²(x-2)-3(x-2)=(x-2)(x²-3)=(x-2)(x-pier.z3)(x+pierw.z 3)

miejsca: x=2 i x=pierwiastek z 3 i x=-pierwiastek z 3